DEVELOPMENT OF CREATIVE PERSONAL ABILITIES IN CONTINUOUS EDUCATION - Marchenko, N.; Subina, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article describes the basic principles of continuing education, which consist in the systematic combination of self-education, optimal distribution of time, human-centrism, creativity, self-reflection. The main attention is paid to the analysis of the constituent elements of the creative personality of adults. The authors analyze the factors and methods of developing creative potential in the context of continuing education. The reason for the creation of creativity is the contradiction between what is already known (stereotype) and the generation of original ideas for solving the problem. It is revealed that the driving force of personality development is to a greater extent external and internal motivation. Self-motivation is connected with acquiring information in the framework of personal interests, a sense of satisfaction from the results of successful operation of new knowledge, career growth, value in the labour market, socialization of personality. The exploration also outlines the possible structure of the creative personality of an adult student, which, according to the authors, includes the cognitive and motivational component, as well as the personal qualities of the person. Conditions and means of development of personality's creative abilities within the framework of formal and nonformal education are analyzed. It is argued that in this perspective a significant influence on the student has an environment in which the acquisition of new knowledge and their use, as well as active and non-standard methods used by the teacher during the full-time or distance learning process. It is revealed that problematic learning contributes to the dynamics of creative thinking of the individual, versatile analysis of the situation and creative problem solving, the ability to discuss and adopt other constructive ideas. The article also states that one of the ways to develop the creative abilities of adults is to develop their own projects, business plans, writing articles that reveal work experience, theoretical and practical provisions of the next developments.
Keywords: creativity, motivation, problem-based learning, business games, imitation methods